Key Drivers Behind the Growth of the Polish Packaging Market in 2005-2012 - Macroeconomic Approach - Kowalska, Agnieszka (Olsztyn Economic Journal, 2014)
The Polish packaging industry has been developing dynamically in recent years, and it is the largest packaging market in Europe with estimated value of EUR 6 billion, i.e. 2% of Poland’s GDP. The key macroeconomic factors responsible for the growth of the Polish packaging market are: socioeconomic situation, international trade in goods, production of packaged goods, demographic and market factors. An analysis of the above factors points to the high potential and prospects of the Polish packaging market.